Cellular autofluorescence is magnetic field sensitive - Ikeya, Noboru (Proc Natl Acad Sci U S A, 2021)
We demonstrate, by direct, single-cell imaging kinetic measurements, that endogenous autofluorescence in HeLa cells is sensitive to the application of external magnetic fields of 25 mT and less. We provide spectroscopic and mechanistic evidence that our findings can be explained in terms of magnetic field effects on photoinduced electron transfer reactions to flavins, through the radical pair mechanism. The observed magnetic field dependence is consistent with a triplet-born radical pair and a B(1/2) value of 18.0 mT with a saturation value of 3.7%.